The determinant factors influencing accounting students’ interest in tax career - Umi Sulistiyanti; Sheila Kurniawan; Arif Fajar Wibisono (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2022)
This research is to examine the influences of professional perception, self-ability, career expectation, and brevet tax training on the students’ interest in tax career. The population of this research is Class 2017 and Class 2018 students of Accounting Study Program of Universitas Islam Indonesia. The number of samples is 90 students who were collected using purposive sampling method based on the criteria of having completed the taxation subject and brevet tax training. The data processing tool employed was IBM SPSS version 25. The findings show that professional perception, career expectation, and brevet tax training positively affect the interest of accounting students to have career in tax. However, self-ability does not show any influence on the students’ interest to have career in tax. This Research is expected to be a consideration for educational institutios to motivate students to have a career in taxation.